Type III Methyltransferase M.NgoAX from Neisseria gonorrhoeae FA1090 Regulates Biofilm Formation and Interactions with Human Cells - Kwiatek, Agnieszka; Mrozek, Agnieszka; Bacal, Pawel; Piekarowicz, Andrzej; Adamczyk-Popławska, Monika (Frontiers in Microbiology, 2015)
Neisseria gonorrhoeae is the etiological factor of the sexually transmitted gonorrhea disease that may lead, under specific conditions, to systemic infections. The gonococcal genome encodes many Restriction Modification (RM) systems, which main biological role is to defend the pathogen from potentially harmful foreign DNA. However, RM systems seem also to be involved in several other functions. In this study, we examined the effect of inactivation the N. gonorrhoeae FA1090 ngo0545 gene encoding M.NgoAX methyltransferase on the global gene expression, biofilm formation, interactions with human epithelial host cells and overall bacterial growth. Expression microarrays showed at least a two-fold deregulation of a total of 121 genes in the NgoAX knock-out mutant compared to the wt strain under standard grow conditions. As determined by the assay with crystal violet, the NgoAX knock-out strain formed a slightly larger biofilm biomass per cell than the wt strain (OD570/600 = 13.8  2.24 and 9.35  2.06, respectively). SCLM observations showed that the biofilm formed by the gonococcal ngo0545 gene mutant is more relaxed and dispersed than the one formed by the wt strain. Thickness of the biofilm formed by both strains was 48.3 (14.9) µm for the mutant and 28.6 (4.0) µm for the wt. This more relaxed feature of the biofilm in respect to adhesion and bacterial interactions seems advantageous for pathogenesis of the NgoAX-deficient gonococci at the stage of human epithelial cell invasion. Indeed, the overall adhesion of mutant bacterial cells to human cells was lower than adhesion of the wt gonococci (adhesion index = 0.672 ( 0.2) and 2.15 ( 1.53), respectively); yet, a higher number of mutant than wt bacteria were found inside the Hec-1-B epithelial cells (invasion index = 3.38 ( 0.93)  105 for mutant and 4.67 ( 3.09)  104 for the wt strain). These results indicate that NgoAX-deficient cells have lower ability to attach to human cells, but more easily penetrate inside the host cells. All these data suggest that the NgoAX methyltransferase, may be implicated in N. gonorrhoeae pathogenicity, involving regulation of biofilm formation, adhesion to host cells and epithelial cell invasion.